Percutaneous Venous Cannulation for Minimally Invasive Cardiac Surgery: The Safest and Effective Technique Described Step-by-Step - Pozzoli, Alberto; Torre, Tiziano; Toto, Francesca; Theologou, Thomas; Ferrari, Enrico; Demertzis, Stefanos (Frontiers in Surgery, 2022)
The current cardiac surgical landscape, with the expansion of minimally invasive operations, ECMO, and some interventional therapies, requires a thorough knowledge of peripheral cannulation techniques. In particular, venous cannulation may appear trivial and complication-free, but this does not reflect the reality. A venous cannulation which is not perfectly performed can lead to serious life-threatening complications in several steps. The technique we describe step by step is the current gold standard in terms of safety and efficacy: from the use of ultrasound for ultrasound-guided puncture to safe advancement of super stiff guidewires by means of a sentinel catheter, and concluding with smooth insertion of the venous cannula over the stiff guidewire up to the SVC. Moreover, a list of bailout maneuvers to solve complications is presented along with a report of institutional clinical experience since the adoption of this technique.